Agronomic and Physiological Adaptation of Robusta Coffee Clone BP-308 to Lampung Highland Conditions - Sari, Sismita; Nurmayanti, Sri; Widiani, Dimas Prakoswo; Erfandari, Ovy; Fajriani, Annisa Fitri (Biotropika: Journal of Tropical Biology, 2026)
The agronomic and physiological characteristics of Robusta coffee, particularly in superior clones, are essential for assessing growth potential, productivity, and adaptability. This study aimed to evaluate the differences in the agronomic and physiological responses of the Robusta coffee clone BP-308 at different altitudes. The research was conducted in two locations: Ulu Belu District (557 m a.s.l.) and Tribudi Syukur Village, Kebun Tebu District, West Lampung Regency (877 m a.s.l.). Field observations were carried out using a survey and direct measurement approach, and data were analysed descriptively and inferentially using the Shapiro–Wilk, Levene, and ANOVA tests, followed by the Least Significant Difference (LSD) test at a 5% significance level. Pearson correlation analysis was also performed to assess the relationships between environmental factors and various plant traits. The results indicated that altitude significantly affected plant height and primary branch length, while physiological traits such as chlorophyll and leaf nitrogen were higher at lower elevations. Coffee plants at 877 m a.s.l. showed greater chlorophyll and nitrogen content, while those at 557 m a.s.l. exhibited stronger structural growth. It is concluded that Robusta clone BP-308 performs optimally at mid- to low-altitude areas, with adaptive agronomic management recommended to maximise productivity and physiological efficiency.